Bound states in the continuum based on the total internal reflection of Bloch waves. Issue 1 (4th March 2022) - Hu, Peng; Xie, Chongwu; Song, Qianju; Chen, Ang; Xiang, Hong; Han, Dezhuan; Zi, Jian
ABSTRACT: A photonic-crystal slab can support bound states in the continuum (BICs) that have infinite lifetimes but are embedded into the continuous spectrum of optical modes in free space. The formation of BICs requires a total internal reflection (TIR) condition at both interfaces between the slab and the free space. Here, we show that the TIR of Bloch waves can be directly obtained based on the generalized Fresnel equations proposed. If each of these Bloch waves picks up a phase with integer multiples of 2π for traveling a round trip, light can be perfectly guided in the slab, namely forming a BIC. A BIC solver with low computational complexity and fast convergence speed is developed, which can also work efficiently at high frequencies beyond the diffraction limit where multiple radiation channels exist. Two examples of multi-channel BICs are shown and their topological nature in momentum space is also revealed. Both can be attributed to the coincidence of the topological charges of far-field radiations from different radiation channels. The concept of the generalized TIR and the TIR-based BIC solver developed offer highly effective approaches for explorations of BICs that could have many potential applications in guided-wave optics and enhanced light–matter interactions. Abstract : Formation mechanisms of bound states in the continuum in a photonic-crystal slab are elaborated and formulated based on total internal reflections of Bloch waves, from which a highly efficient solver is developed.